A Case of Topical Ruxolitinib Treatment Failure in Alopecia Areata. Issue 3 (November 2017) - Deeb, Maya; Beach, Renée A.
Alopecia areata (AA) is an autoimmune-mediated, nonscarring form of hair loss. Despite its prevalence, current management options are limited, especially when the disease has progressed to alopecia totalis (AT) or alopecia universalis (AU). Recent evidence that janus kinase (JAK) signaling contributes to AA pathogenesis prompted the investigation of JAK inhibitors such as tofacitinib and ruxolitinib as possible oral treatments. However, the potential for significant adverse effects with systemic JAK inhibition makes local administration a more attractive option. Yet, a paucity of data exists on topical JAK inhibition in AA. A success of topical ruxolitinib (0.6% cream) use in a young patient with AU has been reported to date. Here we report the treatment of a 66-year-old with AA with the same formulation of topical ruxolitinib, where it failed to induce hair growth. Our report demonstrates the importance of examining the factors contributing to variation in treatment response in a clinical trial of topical JAK inhibitors in AA. It is likely that both intrinsic factors specific to individual patients and extrinsic factors relating to treatment regimen are involved. Furthermore, characterisation of the specific JAKs overexpressed in AA may better target medication. Finally, this report highlights the need to compare the outcomes of topical vs oral ruxolitinib administration in patients with severe AA, AT, and AU and may support the possibility that extensive disease is more adequately treated with oral administration of ruxolitinib.